Zeeq un Nafas (Asthma) and their Understanding in the Past: Unani Concept (Global Journal of Science Frontier Research, 2022)
The Unani System of Medicine pioneered in Greece and was developed by Arabs into an elaborate medical science based on the frame work of the teaching of Buqrat Hippocrates and Jalinoos Galen Since that time Unani Medicine has been known as Greco-Arab Medicine This system is based on Hippocratic theory of four humours viz blood phlegm yellow bile and black bile and the four qualities of states of living human body like hot cold moist and dry They are represented as earth water fire and air the Greek ideas were put by Arabian physician as seven principles Umoor-e-Tabbiya and included element Arkan temperament Mizaj humours Akhlat organs Aaza sprit Arwah faculties Qowa and functions Afaal In this system is it believed that these principles are responsible for the body constitution and its health as well as diseased conditions Ishtiyaq 1983 The term ZeequnNafas is composed of two words Zeeq and Nafas meaning narrowing and breathing respectively In other words it means difficulty in breathing ZeequnNafas is mentioned by the ancient physicians and philosophers like Buqrat Hippocrates - 460 377 BC and Jalinus Galen - 129 210 AD Buqrat described this disease as breathlessness khan 2003 In unani classics Ta deel- Mizaj correction of temperament is required and TanqiaMawad cleansing of viscous humour Mulattif MunaffisBalgham and MukhrijBalgham drugs are recommended Sometimes Muqi emetics are recommended for evacuation of Balgham Mohallil-e-Auram and Daf- Tashannuj are also recommended sena 1411 In this article authors describe about the concept risk factors causes pathophysiology and classification of Asthma
Keywords: asthma; unani; unani medicine; greco-roman medicine; prevention; diet